Impact of fitness characteristics on tennis performance in elite junior tennis players - Ulbricht, A.; Fernandez-Fernandez, J.; Mendez-Villanueva, A.; Ferrauti, A. (The Journal of Strength and Conditioning Research, 2016)
The impact of fitness characteristics on tennis performance in adolescent players is not clearly understood. Therefore, the aim of the present study was to test whether physical characteristics are related to players' competitive level (i.e., national youth ranking). A secondary aim was to compare adolescent tennis players by performance level (i.e., regional selected players and the national team). A total of 902 male and female junior players (aged, 11-16 years) in Germany were evaluated using a physical testing battery: grip strength; countermovement jump; 10 and 20-m sprint; tennis-specific sprint; overhead, forehand, and backhand medicine ball throws (MBT); serve velocity and tennis-specific endurance test (hit and turn tennis test). Results showed that serve velocity (r = -0.43 to 0.64 for female subjects [f]; r = -0.33 to 0.49 for male subjects [m]) and upper-body power (e.g., MBT r = -0.26 to -0.49 f; r = -0.20 to -0.49 m) were the most correlated predictors of tennis performance (i.e., national youth ranking) in both female and male tennis players. Moreover, national selected players showed better performance levels than their regional counterparts, mainly in the most predictive physical characteristics (i.e., serve velocity: effect size [ES], 0.78-1.04 f; ES 0.92-1.02 m, MBT: ES, 0.66-0.88 f; ES, 0.67-1.04 m) and specific endurance (ES, 0.05-0.95 f; ES, 0.31-0.73 m). The present findings underline the importance of certain physical attributes, especially serve velocity and strength- and power-related variables (upper body), and suggest the need to include these parameters in the area of training, physical testing, and talent identification of young tennis players.